Utilizing a structured case method in financial accounting within a problem-based learning framework / Jeffrey Faux - Jeffrey, Faux (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
The structured case method is a flexible and adaptive learning approach developed in Advanced Financial Accounting for the primary purpose of meeting student learning needs where knowledge inputs are constantly changing. The use of cases and in particular a structure case approach was adopted to enable students to formulate written responses and learn to problem solve within a designated framework. Initial evaluation of the structured case approach through student surveys and peer review was very positive. Development of the usefulness of the structured case approach can be identified through an alignment with the more far reaching objectives encompassed by problem-based learning. Students were surveyed to determine the effectiveness of the structured case approach from within a problem-based learning framework. Results indicate that the approach provides the conditions for the attainment of general competencies and effective adult learning.